Environment, politics, and society - Alagan, Ramakrishnan; Aladuwaka, Seela (Research in political sociology ;, 2018)
This special volume of Research in Political Sociology addresses the interconnectivity of environment, politics and society. Contributors engage with critical topics such as water resource management, climate change, civil rights, poverty and social inequality, green transportation and brain drain, and examines these issues internationally in North America, South America, Asia and the Middle East. In the midst of vigorous discussions on environmental sustainability and crises that make global communities more vulnerable than ever before, on local, regional, and global scales, the chapters in this volume offer a much-needed dialogue, and will be of interest to politicians, policymakers and scientists as well as academic researchers.